Communication Gaps Associated With Donor‐Derived Infections. Issue 1 (6th November 2014) - Miller, R.; Covington, S.; Taranto, S.; Carrico, R.; Ehsan, A.; Friedman, B.; Green, M.; Ison, M. G.; Kaul, D.; Kubak, B.; Lebovitz, D. J.; Lyon, G. M.; et al.
<x xml:space="preserve">Abstract</x> The detection and management of potential donor‐derived infections is challenging, in part due to the complexity of communications between diverse labs, organ procurement organizations (OPOs), and recipient transplant centers. We sought to determine if communication delays or errors occur in the reporting and management of donor‐derived infections and if these are associated with preventable adverse events in recipients. All reported potential donor‐derived transmission events reviewed by the Organ Procurement and Transplantation Network Ad Hoc Disease Transmission Advisory Committee from January 2008 to June 2010 were evaluated for communication gaps between the donor center, OPO and transplant centers. The impact on recipient outcomes was then determined. Fifty‐six infection events (IEs; involving 168 recipients) were evaluated. Eighteen IEs (48 recipients) were associated with communication gaps, of which 12 resulted in adverse effects in 69% of recipients (20/29), including six deaths. When IEs and test results were reported without delay, appropriate interventions were taken, subsequently minimizing or averting recipient infection (23 IEs, 72 recipients). Communication gaps in reported IEs are frequent, occur at multiple levels in the communication process, and contribute to adverse outcomes among affected transplant recipients. Conversely, effective communication minimized or averted infection in transplant recipients.